Form and Meaning of Ornamental Variety Elements in the Interior Style of Batik Kitchen Café and Restaurant in Cirebon - Rosiana Rosiana; Indarto Indarto (Institut Seni Indonesia Surakarta, 2021)
Batik Kitchen Café and Restaurant is a culinary-related commercial building in Cirebon. Batik Kitchen Café and Restaurant in Cirebon applies decorative elements in the form of batik to its interior style. The application of decorative elements to the interior style of Batik Kitchen Café and Restaurant is found in the elements that form and fill the space. This study aims to determine the application, decoration, and meaning of the decorations in the interior of Batik Kitchen Café and Restaurant in Cirebon. To answer the problems in the study, the interior design approach the theory of D.K. Ching, and Roland Barthes' approach to meaning. The research was conducted with a qualitative descriptive method. This qualitative research is directed at the real conditions of the research object. The data sources of this research are sources (informants), objects, records, literature, and the internet. The results showed: (1) The application of decorative elements in the form of batik was found in space; lobby area, dining room, and bar area, in the form of space-forming elements; floors, walls, and ceilings, as well as space fillers; tables and chairs, as well as interior accessories. (2) The decorative elements applied to the interior style of Batik Kitchen Café and Restaurant in Cirebon is Nusantara batik motifs which have various meanings. The application of decorative elements to the interior style of the Batik Kitchen Cafe and Restaurant in Cirebon which plays a role in introducing, promoting, and preserving the traditional and cultural values of Cirebon City.